Folliculotropic mycosis fungoides in a child: a rare case - Fatima Zahoor; Junaid, Shakila; Ghazal Afzal (Journal of the Pakistan Medical Association, 2023)
Folliculotropic mycosis fungoides (FMF) is a variant of mycosis fungoides characterized by infiltration of hair follicle epithelium by neoplastic lymphoid cells. Generally, it is usually typified by indurated plaques and tumours mainly on the head and neck. However, a wide range of clinical signs have been noted. The clinical presentation of FMF may include prurigo-like lesions, acneiform lesions, cysts, nodules, areas of scarring alopecia, and hypopigmented plaques or papules with follicular prominences. The average age of diagnosis is 60 years while it is rare in childhood and adolescence. We discuss the case of a 12-year-old boy patient who had an asymptomatic, erythematous, infiltrating plaque across his left nasolabial fold for three months prior to presentation. Histological assessment of lesion showed characteristic findings of follicular mucinosis with predominance of CD4+ lymphocytes and immunohistochemical studies were positive for CD3+ stains. An increased CD4:CD8 ratio and negative CD20 was also shown. —Continue